Plan de manejo para la reserva parroquial Amuicha Entsa ubicada en la parroquia Timbara y San Carlos de Las Minas - Ordoñez Zaruma, Neison Leonardo (2015)
The reserve Amuicha Entsa parish is located in the parishes of Timbara and San Carlos of the mines, belonging to the province of Zamora Chinchipe, where there is a wide variety of species, flora, fauna and water resources, and they have been recognized for its diversity and natural resources that should be preserved and protected because there is a biological connectivity with other conservation areas surrounding. With the purpose of conserving this area this thesis was to develop a management plan in SENPLADES format for the ecological reserve Amuicha Entsa parish, whose objectives were to validate the information obtained from the base line of the study of alternatives 2013, Analyze the different potentials and limitations, was finally drafted a proposal to Management Plan, which enables the active participation and deliberate by the people in the decisions of management of the area and the need to promote a worthy development for the population within the buffer zone. It promotes different components with their respective activities that allow you to contribute to the sustainable management of the ecological area to strengthen the level of organization of local communities, promoting research, promoting sustainable production alternatives for the buffer zone and create environmental awareness in the uses of natural resources. With the foregoing the development of this management plan for the reserve, will allow you to generate a joint effort between the communities that are in the buffer zone and institutions, thus creating an economic benefit in a sustainable manner and at the same time allows you to conserve the natural resources of the Reserve Amuicha parish Entsa